Finance against Poverty. Volume 2 - David Hulme; Paul Mosley (Routledge, 1996)
Over the last decade, the theory that poverty in the world's poorest regions could be alleviated by providing small loans to micro-entrepreneurs has become increasingly popular. This volume examines the effectiveness of this theory when put into practice. The book presents empirical evidence drawn from comparative experiences in seven developing countries and produces some startling conclusions. This work should be essential reading for all those interested in development, poverty-reduction, social welfare and finance. Volume One provides a detailed analysis of this theory and offers policy recommendations for practitioners in the field.
Keywords: 330